The Eco-Pedagogical Microforest a shared oasis of proximity. A cutting-edge project at the intersection of ecology, urbanism and pedagogy - Fratini, Fabiola (TeMA - Journal of Land Use, Mobility and Environment, 2023)
Cities and urban areas are one of the critical global systems that can accelerate and upscale climate action and more than ever need to achieve the 11 goals of Agenda 2030 becoming inclusive, safe, resilient and sustainable. In 2019, Science published a paper suggesting that planting trees, on a massive scale and sustained period of time, represented one of the most effective solutions at our disposal to mitigate climate change. Cities across the world have started implementing urban forests to address multiple environmental issues. Urban forests are capable to provide more complete solutions than other urban NBS. In this context, the challenge for cities is to disseminate UF-NBS throughout the city in order to release environmental and social benefits even in the most dense areas, spreading wellbeing for all citizens. The paper illustrates a cutting-edge experimentation of a tiny forestation action at the neighborhood scale, aimed at integrating both regulative and social-cultural ecosystem services. In line with the principles of the UN Agenda 2030, the Eco-Pedagogical Microforest project, that took place in Rome, demonstrates that even a small patch of nature can increase young people’s biospheric values, influencing pro-environmental behaviors and actions, enhancing wellbeing.